A history of women's writing in Russia - Barker, Adele Marie, 1946-; Gheith, Jehanne M. (Cambridge, UK ; New York : Cambridge University Press, 2002)
A comprehensive account of the lives and works of Russia's women writers from the Middle Ages to the present. Contributors have addressed the surprising contexts within which women's writing has been produced. The volume is supported by extensive reference features including a bibliography and guide to writers and their works.
Women's image in Russian medieval literature / Rosalind McKenzie -- Sappho, Corinna, and Niobe: genres and personae in Russian women's writing, 1760-1820 / Catriona Kelly -- The inexperienced muse: Russian women and poetry in the first half of the nineteenth century / Judith Vowles -- Women of the 1830s and 1850s: alternative periodizations / Jehanne Gheith -- "A particle of our soul": pre-Revolutionary autobiography by Russian women writers / Mary Zirin -- The women of Russian Montparnasse (Paris, 1920-1940) / Catherine Ciepiela -- Women in Russian symbolism: beyond the algebra of love / Jenifer Presto -- The eastern path of exile: Russian women's writing in China / Olga Bakich, Carol Ueland -- Realist prose writers, 1881-1929 / Rosalind Marsh -- Women and gender in post-symbolist poetry and the Stalin era / Katherine Hodgson -- Writing the female body politic (1945-1985) / Beth Holmgren -- In their own words? Soviet women writers and the search for self / Anna Krylova -- Women's poetry since the sixties / Stephanie Sandler -- The persistence of memory: women's prose since the sixties / Adele Marie Barker -- Perestroika and post Soviet prose: from dazzle to dispersal / Helena Goscilo.
Includes bibliographical references (pages 313-379) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Russian literature -- Women authors -- History and criticism; Women -- Soviet Union -- Intellectual life; Women -- Russia -- Intellectual life; Women and literature -- Soviet Union; Women and literature -- Russia; Russian literature -- History and criticism; Women -- Russia (Federation) -- Intellectual life; Littérature russe -- Histoire et critique; Femmes et littérature -- Russie -- Histoire; Femmes -- Russie -- Vie intellectuelle; Femmes -- URSS -- Vie intellectuelle; Écrits de femmes russes -- Histoire et critique; Femmes et littérature -- URSS; Femmes et littérature -- Russie; LITERARY CRITICISM -- Russian & Former Soviet Union; Russian literature -- Women authors; Women and literature; Women -- Intellectual life; Russia; Soviet Union; Frauenliteratur; Schriftstellerin; Russisch; Criticism, interpretation, etc